Social Satire in Harold Pinter's Celebration - مؤيد انوية ججو مروة غازي محمد (College of Education for Women, 2019)
Harold Pinter was one of the most important dramatists in the modern and the contemporary age. Pinter presented his own dramatic realm in which he turns the theatre into a moral institution. He employed the elements of several schools of drama and manipulated them in order to deliver his ethical messages emphasizing the necessity to regain and renew the world's morality in order to face the political and social injustices committed against humanity. His writings developed over more than fifty years in style, techniques and his interests. However, his main concern was his social and political satire.